Evaluation of in vivo behavior of controlled and pulsatile release pastilles using pharmacokinetic and γ-scintigraphic techniques - Shukla D.; Chakraborty S.; Mishra B. (My University, 2025)
Objective: To evaluate the in vivo behavior of controlled and pulsatile release pastilles for chronic treatment of asthma and chronic obstructive pulmonary disease (COPD) and for the chronotherapeutic management of nocturnal asthma, respectively. Research design & methods: The prepared immediate release and controlled release pastilles were subjected to in vivo pharmacokinetic studies in rats. Whereas, pulsatile release formulation was subjected to γ-scintigraphic study in rats to study the gastrointestinal transit of the formulations and its results were correlated with the previous pharmacokinetic data. Results: The in vivo pharmacokinetic study of controlled release pastille formulation showed significant decrease in Cmax with increase in tmax, which indicates that the effect of dosage form would last for longer duration. Thus, the prepared formulation can be useful for the chronic treatment of asthma and COPD. The γ-scintigraphic study and pharmacokinetic data indicated that the pastilles coated with the enteric coat and the additional floating coat were effective in significantly delaying the in vivo drug release (by 45 h) required for the chronotherapeutic treatment of nocturnal asthma. Conclusion: This study opens a new alternative to the conventional tablet or capsule dosage form for the development of both immediate and modified release drug delivery systems. © Informa UK, Ltd.